Micro Change Agents for Gender Equality: Transforming European Research Performing Organizations - Dahmen-Adkins, Jennifer; Peterson, Helen (Frontiers in Sociology, 2021)
This article explores the experiences of micro change agents for gender equality in seven European Research Performing Organizations in seven different countries. The micro change agents were all participants of an international collaborative project consortium, implementing gender equality plans (GEPs), and funded by the European Commission during 4 years. The analysis draws on empirical data consisting of information submitted by the micro change agents during these 4 years and collected using three different monitoring tools, developed within the project to follow the progress of the implementation efforts, but also to provide an arena for individual and collaborative reflection and knowledge exchange between the partners. The aim of the article is to present a systematic analysis of the change practices that these micro change agents experienced as useful and important for promoting gender equality in their different organizational contexts. A total of six such micro change practices are identified, emerging from the empirical data: 1. communicating, 2. community building, 3. building trust and legitimacy, 4. accumulating and using resources, 5. using and transferring knowledge, and 6. drawing on personal motivation. The findings illustrate the multifaceted character of micro change agency for gender equality, particularly in a time-limited project context with a designated funding period. The results from this study can be useful when developing gender equality strategies, policies and practices and can also be used to empower gender equality micro change agents that face challenges while trying to implement GEPs and promote structural change in any kind of institution.